Дорога: [роман] - Маринина Александра Борисовна (А. Маринина - королева детектива, 2009)
Экземпляры: ф.8 (2010) / Инвентарный номер: 53213 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44